2017
DOI: 10.1161/circgenetics.116.001678
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Signature of Cigarette Smoking and Evidence for a Putative Causal Role of MicroRNAs in Smoking-Related Inflammation and Target Organ Damage

Abstract: Background Cigarette smoking increases risk for multiple diseases. MicroRNAs (miRNAs) regulate gene expression and may play a role in smoking-induced target organ damage. We sought to describe a miRNA signature of cigarette smoking and relate it to smoking-associated clinical phenotypes, gene expression, and lung inflammatory signaling. Methods and Results Expression profiling of 283 miRNAs was conducted on whole blood-derived RNA from 5,023 Framingham Heart Study participants (54.0% women, mean age 55±13 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 86 publications
2
42
1
Order By: Relevance
“…Moreover, all the recruited athletes presented similar performance‐related parameters as directly measured by maximal oxygen consumption (53 ± 9 vs. 57 ± 6 mL/kg/min), weekly training hours (7 ± 1 vs. 9 ± 4), and sport vintage (12 ± 6 vs. 15 ± 6). As microRNA parameters might change after smoking‐related inflammation, only non‐smoker subjects were included in this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, all the recruited athletes presented similar performance‐related parameters as directly measured by maximal oxygen consumption (53 ± 9 vs. 57 ± 6 mL/kg/min), weekly training hours (7 ± 1 vs. 9 ± 4), and sport vintage (12 ± 6 vs. 15 ± 6). As microRNA parameters might change after smoking‐related inflammation, only non‐smoker subjects were included in this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It is plausible that differences in noncoding RNA may be a result of this change. Willinger et al [2017] reported that 6 microRNAs (miR-1180, miR181a-2-3p, miR-423-5p, miR-25-5p, miR-1285-3p, miR-342-5p) were significantly related to a three-level smoking status, and they further found that these miRNAs have negative associations with the serum concentration of C reactive protein. Interestingly, in the cancer study, tobacco-dysregulated noncoding RNAs were related to clinical characteristics in head and neck squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…The miRNA dysregulation has been linked to EBV infection and cigarette smoking in several studies, while vitamin D supplementation was found to regulate the miRNA populations. [108][109][110][111][112][113][114][115][116][117][118][119][120][121][122] MS has been associated with many dysregulated miRNAs with disease modulating effects. 111,117,[123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140] Finding the link between these two groups, environmental factors and miRNAs, may explain the risk of environmental factors on MS pathogenicity.…”
Section: Mohammedmentioning
confidence: 99%
“…161 Smoking is also implicated in the upregulation of miR-342, which is known to distinguish RRMS and progressive MS from controls and RRMS from progressive MS (Tables 1 and 2). 118,127 miR-342 has been shown to promote inflammatory activation of MØ. 118 Interestingly, this miRNA can target several genes, including TNFRSF6B, TRAF3, and KIF21B, which was proved to pose a risk towards MS in the IMSGC study (Table 3).…”
Section: Data Extractionmentioning
confidence: 99%